2002
DOI: 10.1093/molehr/8.12.1117
|View full text |Cite
|
Sign up to set email alerts
|

Expression and subcellular distribution of the active form of c-Src tyrosine kinase in differentiating human endometrial stromal cells

Abstract: Decidual growth factors and locally produced cytokines are thought to activate specific phosphorylation signalling pathway(s), thereby eliciting a variety of decidual functions. We have previously reported the activation of c-Src tyrosine kinase during ovarian steroid-induced decidualization of cultured human endometrial stromal cells. As chicken c-Src is known to be activated upon dephosphorylation of tyrosine 527 (Y527, corresponding to Y530 in human), we here employed a monoclonal antibody, clone 28, direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 43 publications
3
15
0
Order By: Relevance
“…This interaction may be facilitated when SRC becomes conformationally open upon dephosphorylation of tyrosine 527 (530 in human). In agreement, with this, we previously reported that decidual SRC becomes activated together with its dephosphorylation on tyrosine 530 [67,72]. Furthermore, it is likely that SRC activation is hormone dependent in decidual hESCs, as withdrawal of E2 and progesterone reduces SRC kinase activity to its basal level and also changes the pattern of tyrosine phosphorylation to that of the unstimulated state [66].…”
Section: D]pyrimidine (Pp1) and 4-amino-5-(4-chlorophenyl)-7-(t-butylsupporting
confidence: 85%
See 1 more Smart Citation
“…This interaction may be facilitated when SRC becomes conformationally open upon dephosphorylation of tyrosine 527 (530 in human). In agreement, with this, we previously reported that decidual SRC becomes activated together with its dephosphorylation on tyrosine 530 [67,72]. Furthermore, it is likely that SRC activation is hormone dependent in decidual hESCs, as withdrawal of E2 and progesterone reduces SRC kinase activity to its basal level and also changes the pattern of tyrosine phosphorylation to that of the unstimulated state [66].…”
Section: D]pyrimidine (Pp1) and 4-amino-5-(4-chlorophenyl)-7-(t-butylsupporting
confidence: 85%
“…Furthermore, we found that tyrosine kinase activity of SRC was increased during in vitro decidualization [66]. Subsequent immunohistochemical studies of the human endometrium and pregnancy decidua revealed that the kinase-active form of SRC was strongly expressed in decidual cells in humans and mice [67,68].…”
Section: Downstream Events Of Camp Signalingmentioning
confidence: 82%
“…For example, dephosphorylation of Src Tyr-530 by protein tyrosine phosphatases has been proposed as a likely mechanism for its activation (15). Interestingly, Src was found to be dephosphorylated at its inhibitory site Tyr-530 in our phosphoproteome, suggesting potential involvement of β-arrestins in activation of Src in response to AT1aR activation.…”
Section: β-Arrestin-dependent Phosphorylation Events Downstream Of At1armentioning
confidence: 80%
“…Our data for active and total Src kinase expression mainly in the cytoplasm of epithelial and stromal cells is similar to what was found by Reissig et al (16), who also demonstrated positive staining for active Src in both glandular epithelium and stromal compartments of breast carcinoma tissues. Yamamoto et al (26) found that in proliferative endometrium, active Src expression was detected mainly in glandular epithelium and that stromal Src exhibited perinuclear localization. In secretory phase endometrium, active Src was detected in both the stroma and glandular epithelium (26).…”
Section: Discussionmentioning
confidence: 99%